An Analysis of Lexical Cohesion Found in “Photograph” Song Lyrics - Ni Kadek Ayu Anggreni Putri (Linguistics Initiative, 2022)
The aim of this study is to find out the type and function of lexical cohesion used in the lyrics of Ed Sheeran's song entitled "Photograph" based on the theory of lexical cohesion. This study uses a qualitative method that focuses on the type of lexical cohesion, especially repetition (anaphora and epistrophe repetition), the synonym, antonym, and collocation. The researcher used observation with note-taking techniques to collect data. The results of this study are found all the types of lexical cohesion in the song lyrics entitled "Photograph". In Reiteration, the writer found 16 repetitions (anaphora and epistrophe repetition), 2 synonyms, 5 antonyms, and 1 collocation. So, it can be deduced that the most lexical cohesion that appears in the song lyrics entitled "Photograph" is Repetition. The lexical cohesion that emerges in the lyrics of the song, will make it more harmonious and meaningful.